2003
DOI: 10.1097/00004032-200308000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patient and Staff Doses During Various Ct Fluoroscopy Guided Interventions

Abstract: As CT scanners are more routinely used as a guidance tool for various types of interventional radiological procedures, concern has grown for high patient and staff doses. CT fluoroscopy provides the physician immediate feedback and can be a valuable tool to dynamically assist various types of percutaneous interventions. However, the fixed position of the scanning plane in combination with high exposure factors may lead to high cumulative patient skin doses that can reach deterministic threshold limits. The sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 24 publications
0
56
1
2
Order By: Relevance
“…This means that it would take over 2000 CT interventions to reach the annual limit value. In the study by Buls et al (2003), the median hand dose for the right hand was 0.76 mSv which is significantly higher than our measured values [19]. However, our values were significantly higher than those of Stoeckelhuber et al…”
Section: Hand Dose Valuescontrasting
confidence: 78%
“…This means that it would take over 2000 CT interventions to reach the annual limit value. In the study by Buls et al (2003), the median hand dose for the right hand was 0.76 mSv which is significantly higher than our measured values [19]. However, our values were significantly higher than those of Stoeckelhuber et al…”
Section: Hand Dose Valuescontrasting
confidence: 78%
“…A topic of interest in future lens dose research is CT fluoroscopy, which is known to deliver higher radiation doses than single-slice CT acquisition [43]. One study found that, over 82 consecutive procedures, CT fluoroscopy delivered a median per procedure eye level dose of 0.21 mSv [44]. Another study analyzing 220 CT fluoroscopy procedures found a low operator lens dose of 0.010 mSv/procedure, likely due to selection of a low milliampere value and usage of a quick-check technique similar to conventional CT [45].…”
Section: Quantifying Lens Exposure In Interventional Radiologymentioning
confidence: 99%
“…Since the introduction of CT fluoroscopy, operator radiation exposure during CT fluoroscopy-guided intervention has been investigated in a number of studies, most commonly biopsy and drainage procedures [2][3][4][5][6][7][8][20][21][22][23][24]. Although some investigators estimated operator radiation dose using data from phantom measurements [20][21][22][23][24], the estimated dose may not represent actual radiation dose because the distance between the operator and CT gantry often changes during procedures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, operator radiation exposure is a substantial disadvantage of CT fluoroscopy-guided procedures. Operator radiation dose has been measured in previous studies for various CT fluoroscopy-guided interventional procedures, most commonly biopsy and drainage [2][3][4][5][6][7][8]. However, data on operator dose during ablation procedures are lacking.…”
Section: Introductionmentioning
confidence: 99%